Influencia del programa Cuna Más, en la dinámica familiar de los usuarios, base “Semillitas Viruñeras” Distrito de Virú, 2022 - Palacios Quispe, Tania Kimberly Viviana (2023)
The objective of this research work is to analyze the influence of the Cuna Más program on the family dynamics of the users, base "Semillitas Viruñeras" in the District of Virú, 2022. This research corresponds to a mixed approach, where the qualitative and quantitative approach was used, the population was made up of 25 beneficiary families. Likewise, with a deductive, inductive, statistical and analytical methodology; using as techniques, the interview, the survey and the observation; having as instruments, interview guide, interview record, questionnaire and observation guide. One of the main results of this research corresponds to the fact that the Cuna Mas "Semillitas Viruñeras" program positively influences the family dynamics of the users, through the strengthening of cohesion, according to the results, 56% of the Mothers of families take into account the importance of establishing healthy bonds of affection, evidenced by sharing quality time and paying more attention to the feelings of their children through manifestations of love, thus achieving optimal affective development in beneficiary children. Finally, it is recommended that those in charge of the Cuna Mas program identify support networks with local authorities and link to the needs of the people, with the purpose that the population is aware of the benefits provided by the program, allowing more users to be beneficiaries and continue to promote proper child development for children in the province of Viru.